Metatranscriptomics reveals a differential temperature effect on the structural and functional organization of the anaerobic food web in rice field soil - Jingjing Peng; Carl-Eric Wegner; Qicheng Bei; Pengfei Liu; Werner Liesack (Microbiome, 2018)
Abstract Background The expected increase in global surface temperature due to climate change may have a tremendous effect on the structure and function of the anaerobic food web in flooded rice field soil. Here, we used the metatranscriptomic analysis of total RNA to gain a system-level understanding of this temperature effect on the methanogenic food web. Results Mesophilic (30 °C) and thermophilic (45 °C) food web communities had a modular structure. Family-specific rRNA dynamics indicated that each network module represents a particular function within the food webs. Temperature had a differential effect on all the functional activities, including polymer hydrolysis, syntrophic oxidation of key intermediates, and methanogenesis. This was further evidenced by the temporal expression patterns of total bacterial and archaeal mRNA and of transcripts encoding carbohydrate-active enzymes (CAZymes). At 30 °C, various bacterial phyla contributed to polymer hydrolysis, with Firmicutes decreasing and non-Firmicutes (e.g., Bacteroidetes, Ignavibacteriae) increasing with incubation time. At 45 °C, CAZyme expression was solely dominated by the Firmicutes but, depending on polymer and incubation time, varied on family level. The structural and functional community dynamics corresponded well to process measurements (acetate, propionate, methane). At both temperatures, a major change in food web functionality was linked to the transition from the early to late stage. The mesophilic food web was characterized by gradual polymer breakdown that governed acetoclastic methanogenesis (Methanosarcinaceae) and, with polymer hydrolysis becoming the rate-limiting step, syntrophic propionate oxidation (Christensenellaceae, Peptococcaceae). The thermophilic food web had two activity stages characterized first by polymer hydrolysis and followed by syntrophic oxidation of acetate (Thermoanaerobacteraceae, Heliobacteriaceae, clade OPB54). Hydrogenotrophic Methanocellaceae were the syntrophic methanogen partner, but their population structure differed between the temperatures. Thermophilic temperature promoted proliferation of a new Methanocella ecotype. Conclusions Temperature had a differential effect on the structural and functional continuum in which the methanogenic food web operates. This temperature-induced change in food web functionality may not only be a near-future scenario for rice paddies but also for natural wetlands in the tropics and subtropics.